<h2>
Steps</h2><h3>
Equation: 6(4x + 5) + 3 = 3(x + 8) + 3</h3>
Subtract 3 from both sides
6(4x + 5) + 3 - 3 = 3( x + 8) + 3 - 3
Simplify
6( 4x + 5) = 3(x + 8)
<h3>Apply the distributive law:</h3>
6(4x + 5)
<u>a(b + c) = ab + ac</u>
a = 6, b = 4x, c = 5
= 6 x 4x + 6 x 5
<h3>Simplify</h3>
6 x 4x + 6 x 5
Multiply the numbers: <u>6 x 4 = 24</u>
= 24x + 6 x 5
Multiply the numbers: <u>6 x 5 = 30</u>
= 24x + 30
<h3>Apply the distributive law:</h3>
3(x + 8)
<u>a(b + c) = ab + ac</u>
a = 3, b = x, c = 8
= 3x + 3 x 8
Multiply the numbers: <u>3 x 8 = 24</u>
= 3x + 24
24x + 30 = 3x + 24
Subtract 30 from both sides
24x + 30 - 30 = 3x + 24 -30
Simplify
24x = 3x - 6
Subtract 3x from both sides
24x - 3x = 3x - 6 - 3x
Simplify
21x = -6
Divide both sides by 21
21x/21 = -6/21
Note: Simplify -6/21 to get the value for x.
Answer in fraction: x = -2/7
Answer in decimal rounded to the nearest hundredth: x = -0.29
I know this seems complicated; that's why I did it step by step.
<u />